Chaperones of the endoplasmic reticulum are required for Ve1‐mediated resistance to Verticillium. (10th September 2013) - Liebrand, Thomas W. H.; Kombrink, Anja; Zhang, Zhao; Sklenar, Jan; Jones, Alexandra M. E.; Robatzek, Silke; Thomma, Bart P. H. J.; Joosten, Matthieu H. A. J.
Summary: The tomato receptor‐like protein (RLP) Ve1 mediates resistance to the vascular fungal pathogen Verticillium dahliae . To identify the proteins required for Ve1 function, we transiently expressed and immunopurified functional Ve1‐enhanced green fluorescent protein (eGFP) from Nicotiana benthamiana leaves, followed by mass spectrometry. This resulted in the identification of peptides originating from the endoplasmic reticulum (ER)‐resident chaperones HSP70 binding proteins (BiPs) and a lectin‐type calreticulin (CRT). Knock‐down of the different BiP s and CRT s in tomato resulted in compromised Ve1‐mediated resistance to V. dahliae in most cases, showing that these chaperones play an important role in Ve1 functionality. Recently, it has been shown that one particular CRT is required for the biogenesis of the RLP‐type Cladosporium fulvum resistance protein Cf‐4 of tomato, as silencing of CRT3a resulted in a reduced pool of complex glycosylated Cf‐4 protein. In contrast, knock‐down of the various CRT s in N. benthamiana or N. tabacum did not result in reduced accumulation of mature complex glycosylated Ve1 protein. Together, this study shows that the BiP and CRT ER chaperones differentially contribute to Cf‐4‐ and Ve1‐mediated immunity.